Kollektiv kreativitet i forestillinger - Böhnisch, Siemke (Peripeti, 2011)
Collective Creativity in Performances The potential for collective creativity entailed in a conspicuous audience style is examined in this article. In a constructivist approach the article focuses on the difference between inexperienced first-time spectators and the outer theatre frame as a cultural construct. This difference can trigger interruptions and instability. A paradox is seen in the fact that instability is decisive for creativity, but at the same time can be destructive and hard to handle. The article describes how specific interspaces are used in performances for very young audiences in order to make instability both possible and tolerable.